UNDERSTANDING LOCAL COMMUNITIES PERCEPTIONS TOWARDS THE CONSERVATION OF THE ENDEMIC MOLUCCAN MEGAPODE (Eulipoa wallacei) ON HARUKU ISLAND, INDONESIA - Handy Erwin Pier Leimena; Achmad Sjamidi; Tati Suryati Syamsudin (Media Konservasi, 2022)
Assessment of conservation community perceptions has been an important aspect of wild species research. Harvesting the eggs of Moluccan megapodes has implications for the preservation of bird populations. This study aims to assess the perceptions of local communities living near bird nesting sites regarding the conservation of the endemic Moluccan megapodes (Eulipoa wallacei). The survey was conducted on 200 respondents from the productive age group (aged 15 to 65) using a proportionate stratified random sampling technique with a closed-ended questionnaire. The Likert scale was used to analyze perception data. Research findings indicated that the majority of the community supported the practice of harvesting eggs, even though they were aware that the birds were protected species. Community perceptions of conservation only focused on adult birds and their habitat rather than conserving bird eggs. Therefore, the perceptions of egg conservation must be considered when developing an effective conservation program. It was recommended to design a conservation program to increase local people’s awareness of the importance of Moluccan megapode conservation through sustainable egg harvesting.